Deteksi Tingkat Cemaran Bakteri Staphylococcus Aureus pada Daging Ayam Broiler yang Dijual di Pasar Tradisional Kota Lhokseumawe - Amirah Amirah; Juwita Sahputri; Zubir Zubir; Cut Khairunnisa (Publikasi Indonesia, 2022)
Chicken meat is a product from poultry farming which is very important for meeting food needs. Foods that are often the cause of S. aureus poisoning include meat, meat products, and poultry. This study aims to determine the quality of broiler meat as seen from the contamination and level of S. aureus bacteria contamination. The research design is a descriptive laboratory test, using the Total Plate Count (TPC) method listed in SNI 2897:2008, carried out at the Fundamental Science Lab. The research sample was broiler chicken as many as 11 samples from RPA in the traditional market of Lhokseumawe city. The examination started with culturing in BPA media, followed by qualitative tests (identification) including Gram staining, coagulase test, and quantitative test (TPC), namely counting S. aureus colonies on BPA media. The results showed that from 11 samples, no growth characteristics of S. aureus were found. The conclusion is that the broiler meat from the Chicken Slaughterhouse (RPA) located in the traditional market of Lhokseumawe city which was tested met the requirements set by SNI regarding S. aureus bacterial contamination.